Improving Care Coordination Between Veterans Health Administration Primary Care Teams and Community Home Health Aide Providers: A Qualitative Study. (April 2023) - Franzosa, Emily; Judon, Kimberly M.; Gottesman, Eve M.; Koufacos, Nicholas S.; Runels, Tessa; Augustine, Matthew; Van Houtven, Courtney H.; Boockvar, Kenneth S.
Effective coordination between medical and long-term services is essential to high-quality primary care for older adults, but can be challenging. Our study assessed coordination and communication through semi-structured interviews with Veterans Health Administration (VHA) primary care clinicians ( n = 9); VHA-contracted home health agencies ( n = 6); and home health aides ( n = 8) caring for veterans at an urban VHA medical center. Participants reported (1) establishing home health services is complex, requiring collaboration between many individuals and systems; (2) communication between medical teams and agencies is often reactive; (3) formal communication channels between medical teams and agencies are lacking; (4) aides are an important source of patient information; and (5) aides report important information, but rarely receive it. Removing structural communication barriers; incentivizing reporting channels and information sharing between aides, agencies, and primary care teams; and integrating aides into interdisciplinary teams may improve coordination of medical and long-term care.